Gestão escolar democrática na percepção de professores de rede estadual de ensino de Santa Catarina: que sentidos? Quais revelações? - Zardo-Morescho, Sandra Maria (2022)
This thesis is based on Democratic School Management from the perception of teachers who work in public schools belonging to the state education network of Santa Catarina. Its main objective is to announce indicators of the presence of Democratic School Management in the basic education school of the state education network of Santa Catarina from the perceptions of its teachers. The problem that drove the research is formulated in the question: What do the perceptions of basic education teachers from the state education network of Santa Catarina reveal about Democratic School Management in the daily life of their schools? The study resorts to Fraser (2002; 2006; 2007) to discuss the concepts of recognition and participatory parity in favor of social justice. The foundation of the terms democracy, educational policy and Democratic School Management was supported by Rosenfield (2007), Saviani (2008; 2017), Cury (2007), Dourado (2007), Esquinsani and Dametto (2018), Lima (2011; 2013; 2014), Mendonça (2001), Oliveira, Moraes and Dourado (2008), Paro (1995; 2016; 2018), Souza (2009; 2012; 2014; 2016), Vieira (2007) and Zavieruka and Bordignon (2016). It also analyzes democratic management based on the following documents: Charter of Goiânia (ANDE; ANPED; CEDES, 1986), Constitution of the Federative Republic of Brazil (BRASIL, 1988), Constitution of the State of Santa Catarina (SANTA CATARINA, 1989), Law of Directives and Bases of Education (BRAZIL, 1996), National Education Plan (BRASIL, 2014), State Education Plan (2015a), Decree nº. 1,794/2013 (SANTA CATARINA, 2013) and Decree nº. 194/2019 (SANTA CATARINA, 2019c). The production of empirical data took place through an online multiple-choice questionnaire, prepared using Google Forms, aimed at teachers from the state education network of Santa Catarina, with a view to capturing perceptions about Democratic School Management. The analysis is based on the following categories: a. Teacher's perception of democratic management; b. Democratic management in daily school life and teacher participation; and c. Implications for the practice of democratic management. The research, with a pluralist epistemological theoretical conception (TELLO; MAINARDES, 2012), is characterized as exploratory, with qualitative and quantitative analysis, based on non-probabilistic sampling. It is based on the analytical-reconstructive method and identifies with the post-structuralist theoretical approach (MAINARDES, 2006). The results suggest that democratic management is materialized in schools, given that most respondents indicated practices and mechanisms that belong to it, emphasizing the relevance of participation and dialogue. However, it is also pointed out that there are professionals who do not recognize the presence of democratic management in their schools, which may be related to the successive government policies that directly influence the dynamics of management, postponing the materialization of a Democratic School Management. It concludes, signaling the importance of democratic management being based on State policies, whose continuity is marked by participation, dialogue, collective decision-making and permanent learning of those who participate in it.